2016
DOI: 10.4328/jcam.3858
|View full text |Cite
|
Sign up to set email alerts
|

Tp-e Interval and Tp-e/QT Ratio in Chronic Renal Failure Patients Requiring Hemodialysis

Abstract: ÖzetAmaç: Kronik renal yetersizlik (KRY) ventriküler aritmi için ana etkenlerden birisidir. Kronik infilamasyon ve diğer faktörler aritmojenik yüzeyin oluşumuna katkıda bulunurlar. Çalışmamızın amacı hemodiyaliz uygulanan KRY hastalarında QT dispersiyonu, hastalarında T dalga zirve ile sonlanım noktası arası mesafe (Tp-e aralığı), Tp-e/QT oranı ve Tp-e/QTc oranını kullanarak ventrikü-ler repolarizasyonu değerlendirmekti. Gereç ve Yöntem: KRY nedeniyle hemodiyaliz tedavisi almakta olan 35 hastanın elektrokardiy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…An increased prevalence of left ventricular dysfunction, autonomic dysfunction, myocyte dysfunction, altered electrolyte metabolism, and cardiac fibrosis may also contribute to arrhythmic risk in patients with kidney disease [ 23 ]. On the contrary, Karaagac et al found that Tp-e/QT values were similar in ESRD patients receiving hemodialysis compared to healthy age and gender matched individuals [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increased prevalence of left ventricular dysfunction, autonomic dysfunction, myocyte dysfunction, altered electrolyte metabolism, and cardiac fibrosis may also contribute to arrhythmic risk in patients with kidney disease [ 23 ]. On the contrary, Karaagac et al found that Tp-e/QT values were similar in ESRD patients receiving hemodialysis compared to healthy age and gender matched individuals [ 24 ].…”
Section: Discussionmentioning
confidence: 99%